Metastable Racemic Ibuprofen Supercooled Liquid - Tuanjia Li; Wangchuan Xiao; Shizhao Ren; Rongrong Xue; Fenghua Chen (Crystals)
Amorphous solid dispersions are good candidates for improving solubility in water and the oral bioavailability of poorly water-soluble active pharmaceutical ingredients (APIs). Amorphous solids become supercooled liquids when the temperature reaches the glass transition temperature (Tg). For APIs with low melting points, Tg can be below room temperature, which makes it difficult to prepare long-term stable amorphous solids. Studies on the physicochemical properties of supercooled liquids shed light on the design of ASDs for APIs with low melting points. Racemic ibuprofen (IBU) supercooled liquid has been detected using differential scanning calorimetry and powder X-ray diffraction during the melt-quenching of IBU at a low temperature (0 °C). In this work, gram-scaled IBU supercooled liquid was prepared using the melt-quenching method, maintaining a liquid state for minutes at room temperature and for hours at 10 °C, as confirmed by visual observation. The Raman spectra, IR spectra, and UV-vis spectra results indicate that the structure of the IBU supercooled liquid is similar to that of an IBU solution instead of IBU Form I. The rate of recrystallization into Form I can be adjusted by controlling the temperature and additives, as confirmed by visual observation. Moreover, long-term stable IBU dispersions, with improved aqueous solubility, were inspired by the IBU supercooled liquid. The IBU supercooled liquid model can guide the preparation of ASDs for low melting point drugs.